Antimicrobial stewardship in community pharmacies: a mixed-methods study - Sharma, Saurabh; Kumar Sahu, Mahendra (Journal of Neonatal Surgery, 2025)
Although international recommendations support the crucial role that pharmacists play in antimicrobial stewardship (AMS) programs, the degree to which pharmacists participate in AMS programs varies by nation. to investigate the roles that pharmacists play in AMS programs in various income levels and to create interventions tailored to the particular context in order to improve the function of clinical pharmacists in AMS in Kerala, India. There is variance in the degree to which pharmacists participate in the program, which is mostly determined by the AMS training they receive and the backing of hospital administration, even if pharmacist-led or driven AMS treatments are improving patient outcomes. Their involvement in the program can be facilitated by a contextually prepared, standardized, and easily accessible AMS training program, pharmacy curricula that are modified to incorporate AMS, and the acknowledgement of pharmacists' role in AMS. This will help to dismantle long-standing hierarchies and professional boundaries. This would be especially helpful in nations where AMS is severely hampered by a lack of doctors with expertise in infectious diseases.